Genetic structure and molecular analysis of the species of the genus Artemisia L. (Asteraceae) distributed in Azerbaijan - Alamdar Mammadov; Sayyara İbadullayeva; Javid Ojaghi; Zarifa Suleymanova; Narmin Sadıgova (International Journal of Secondary Metabolite)
In this study, the phylogenetic relationships and genetic structure of 10 collected genotypes of Artemisia szowitziana (Besser) Grossh and Artemisia fragrans Willd. species from different regions of Azerbaijan were investigated using RAPD primers. A total of 94 amplicons were amplified using selected RAPD primers. Among them 3 band with OPA-02 primers and 12 band with OPW-17 primers were amplified. The highest polymorphism among the investigated RAPD markers was 100, 90.91 and 90%, which has been obtained by OPW-17, OPT-19, and OPT-20 primers, respectively. However, the calculated average value of polymorphism was as high as 72.79% based on 10 different RAPD markers. The average PIC (Polymorphism Information Content) value (0.864) has indicated the rich genetic diversity among the studied samples. The cluster analyses by using Jaccard similarity index and UPGMA method classified all Artemisia L. samples into 6 major groups. Principal Component Analysis (PCA) justified 74.22% of the total variance. Based on the results obtained, it has been observed that there is a wide range of diversity in the molecular level between the population of Artemisia szowitziana (1-2 and 4-6 samples) and Artemisia fragrans (3, 5, 7 and 8, 9, 10 samples) and between population of the Artemisia species in Azerbaijan.